The Case for Animal Spirituality - Part 2: Logical Arguments, Empirical Evidence, and Practical Consequences for Human Society - Cunningham, Paul F. (Journal for the study of religion, nature and culture, 2022)
This is the second part of a two-part article presenting the theoretical and empirical case for nonhuman animal (hereafter, ‘animal’) spirituality. Part 1 discussed the relevance of evolutionary theory and species differences for understanding animals’ capacity to have spiritual experience, conceptual issues related to defining animal spirituality, and methodological considerations regarding analogical reasoning and animal-centered anthropomorphism as heuristic strategies in the study of animal spirituality. Issues related to the question of animal consciousness and the use of evolutionary panentheism as a philosophical/theological frame for theorizing about animal spirituality were discussed. Part 2 examines six biopsychosocial capabilities of animals that are building blocks of human spirituality—cognition, imagination, emotion, moral sense, personality, and value-life (Maslow’s phrase)—and proposes an ontic pluralism of animal spiritualities. Part 2 concludes with a discussion of the wideranging implications for human society of consciously accepting the possibility of animal spirituality and capacity to have spiritual experience.